Manajemen Pendidikan Inklusi Di Sd Kota Medan - Nurdina Hasanah; SalmidaSimaAini Siagian; Syafira Sahara Saleh (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The purpose of this research is to increase understanding of the implementation of inclusive education at SLB Melati Asyiyah, North Sumatra. This research is a quantitative descriptive research method. The research subjects for this study were randomly selected using a sampling technique called purposive sampling. Observations, interviews and documentation all contribute to the data collection methodology. School administration, school boards, special education teachers and students, and parents of students are important members of any special education project. Data analysis techniques include data collection, data reduction, data presentation, and data verification. The results showed that the implementation of inclusive education at SLB Melati Asyiyah was successful. This is supported by data verification using standard scoring rubrics, empirical evidence obtained from observations, interviews, and written documentation showing that education administration at SLB Melati Asyiyah in West Sulawesi is divided into the areas of curriculum management, student administration, and finance. management. It is the teacher's responsibility to adapt teaching and student evaluation strategies to the needs of individual students. In addition, faculty management starts with the help of a faculty needs database, recruitment resources, and selection criteria. The international faculty's responsibilities emphasize cooperation and coordination. The management of resources and facilities is carried out through strategic planning which is informed by supply and demand analysis.